Neonatal Exposure to Hepatitis C Virus Antigens in Uninfected Children Born to Infected Mothers. Issue 1 (January 2018) - Psaros Einberg, Afrodite; Brenndörfer, Erwin Daniel; Frelin, Lars; Hallberg, Lena; Sällberg, Matti; Fischler, Björn
ABSTRACT: Objective: Vertical transmission of hepatitis C virus (HCV) infection is uncommon and occurs in approximately 5% of births from HCV-infected mothers. The reason for the low transmission rate is unclear. We aimed to investigate whether there is evidence of HCV exposure also in the noninfected children born to HCV-infected mothers by the presence of a detectable immune response. Methods: Serum and peripheral blood mononuclear cells from 9 HCV vertically infected children, 32 uninfected children born to HCV infected mothers, and 15 HCV chronically infected mothers, were analyzed. HCV-RNA-negative adults and children were used as controls. HCV-specific T cell responses were analyzed by interferon gamma using an enzyme-linked immunospot assay and 3H-thymidine incorporation assay. HCV antibodies were also analyzed. Results: An HCV-specific T cell response was detected in 73% (11/15) of the HCV-infected mothers, 67% (6/9) of the vertically infected children, 56% (18/32) of the exposed but uninfected children and in 10% and 20% of the control groups, respectively. The 2 groups of HCV-exposed children both had a significantly higher proportion of HCV-specific T cell responders compared to pediatric controls ( P  = 0.01 and P  = 0.02). Conclusions: HCV-specific immune responses were more common in children born to HCV-infected mothers, regardless of the presence of HCV RNA. We conclude that noninfected children born to HCV-infected mothers may have been exposed to HCV antigens. Abstract : Supplemental Digital Content is available in the text